Chile integrates a gendered climate-smart agriculture approach within its national climate-adaptation plan for agriculture - Castellanos, Andrea Estefania; Martinez Baron, Deissy (2025)
The Ministry of Agriculture of Chile has successfully incorporated a gendered climate-smart agriculture (CSA) approach into its updated Climate Change Adaptation Plan for the Silvoagricultural Sector (PACC SAP), with technical support from the Alliance of Bioversity International and CIAT. Gender considerations were integrated through a diagnostic study on gender gaps, such as access to resources and decision-making, and a practical guide for gender inclusion in climate-smart agriculture initiatives. Enhancing climate adaptation by empowering women farmers and rural communities.